2020
DOI: 10.1016/j.jwb.2018.11.003
|View full text |Cite
|
Sign up to set email alerts
|

The role of emotions in intercultural business communication: Language standardization in the context of international knowledge transfer

Abstract: We examine language standardization in a multinational enterprise in the context of international knowledge transfer treated as an act of communication. Based on psychological theories of emotions and a qualitative study of a Chinese owned company with English as a working language, we find that both native and non-native English-speakers experience anxiety in intercultural communication. This triggers emotions that are culturally predisposed affecting communication behavior. We provide a framework within whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 107 publications
(133 reference statements)
1
23
0
Order By: Relevance
“…Their IBCC was also positively associated with EI, which conforms to the study by Q. Wang et al (2018) and Aichhorn and Puck (2017), who stressed the importance of emotion in IBC. Specifically, the subjects' LP positively correlated with their CQS total.…”
Section: Contributions and Implicationssupporting
confidence: 89%
See 2 more Smart Citations
“…Their IBCC was also positively associated with EI, which conforms to the study by Q. Wang et al (2018) and Aichhorn and Puck (2017), who stressed the importance of emotion in IBC. Specifically, the subjects' LP positively correlated with their CQS total.…”
Section: Contributions and Implicationssupporting
confidence: 89%
“…Q. Wang et al (2018) found that both native English speakers and Chinese business practitioners experienced anxiety in IBC and negative language-induced emotions affected their communication behavior. In the Ang et al (2007), who defined cultural intelligence as capability to function effectively in culturally diverse settings.…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…This is the type of trust that is necessary to build relationships outside of the Guanxi system, following written and unwritten rules. In this case, the ratio of possible risks and benefits from these relationships plays a large role (Wang, 2018).…”
Section: Features Of Chinese Communication Stylementioning
confidence: 99%
“…Furthermore, with regard to the limited extent that IB research has addressed code switching, it has mostly been described as a negative behavior that emphasizes and widens the gaps between individuals and units. Empirical accounts (e.g., Neeley, Hinds & Cramton, 2012;Hinds, Neeley & Cramton, 2014;Tenzer, Pudelko & Harzing, 2014;Tenzer & Pudelko, 2015;Wang et al, 2018) center on phenomena such as subgroups switching to their native language during a meeting held in another language, causing other parties present to experience feelings of exclusion or distrust, with repercussions on their willingness to share knowledge. Tenzer and Pudelko (2015) have recently pointed out that engaging in code-switching may be helpful for linguistically less skilled individuals, and that its effects can be moderated by astute managerial action.…”
Section: Introductionmentioning
confidence: 99%